Co-integration and causality between the spot and futures markets: pre and post implementation of NKEAs / Mohamad Azwan Md Isa, Syamsyul Samsudin and Mohd Khairul Ariff Noh. - Md Isa, Mohamad Azwan; Samsudin, Syamsyul; Noh, Mohd Khairul Ariff (Universiti Teknologi Mara Selangor, 2016)
The Tenth Malaysian Plan (RMK10) through the Economic Transformation Programme (ETP) focuses on 12 National Key Economic Areas (NKEAs). One of the key areas is the palm oil industry. Hence, this study is aimed at examining the implication of the ETP/NKEAs (pre and post) towards the crude palm oil (CPO) and its futures (FCPO) markets. The Johansen approach and the Granger test were employed to prove the co-integration and causality respectively between both markets for the period January 2008 to May 2015. Other empirical tests including the correlation analysis and multiple regressions were also conducted in order to investigate the relationship between the CPO price with the FCPO price, trading volume and open interest. The findings from the Johansen test show that there exists a co-integration in the long run between the Malaysian CPO and FCPO markets. The Granger test result indicates that there is causality of FCPO prices on the CPO prices, but not the other way around. In addition, the Regression analysis shows that FCPO price is the only significant factor that affects CPO price whilst the other two independent variables show insignificant results. The findings would be useful to the market regulators, operators and traders in setting their policy and regulations, and also in their decision making process.